Impaired voluntary running capacity of creatine kinase-deficient mice - Momken, Iman (Blackwell Science Inc, 2005)
The creatine kinase system (CK) is important for energy delivery in skeletal and cardiac muscles. The two main isoforms of this enzyme, cytosolic MM-CK and mitochondrial mi-CK, are expressed in a developmental and muscle-type specific manner. Mice deficient in one or both of these isoforms are viable and fertile but exhibit profound functional, metabolic and structural muscle remodelling that primarily affects fast skeletal muscles, which show an increased contribution of oxidative metabolism to contractile function. However, the consequences of these alterations in terms of physical capabilities have not yet been characterized. Consequently, we compared the voluntary exercise capacity of 9-month-old male wild-type (WT), M-CK knockout (M-CK(−/−)), and M-CK and mi-CK double knockout (CK(−/−)) mice, using cages equipped with running wheels. Exercise performance, calculated by total distance covered and by work done during the training period, was more than 10-fold lower in CK(−/−) mice than controls, with M-CK(−/−) mice exhibiting intermediate performance. Similarly, the mean distance run per activation was lower in M-CK(−/−) and even lower in CK(−/−) mice. However, the maximal running speed (V(max)) was lower only for CK(−/−) mice. This was accompanied by severe skeletal muscle mass decrease in CK(−/−) mice, with signs of histological damage that included enlarged interstitial areas, aggregations of mononuclear cells in the interstitium, heterogeneity of myofibre size and the presence of very small fibres. No overt sign of cardiac dysfunction was observed by magnetic resonance imaging during dobutamine stimulation. These results show that metabolic failure induced by CK deficiency profoundly affects the ability of mice to engage in chronic bouts of endurance running exercise and that this decrease in performance is also associated with muscle wasting.